Dataset: Strong isoprene emission response to temperature in tundra vegetation - Seco, Roger; Holst, Thomas; Davie-Martin, Cleo L.; Simin, Tihomir; Guenther, Alex; Pirk, Norbert; Rinne, Janne; Rinnan, Riikka (Zenodo, 2022)
Dataset used in the article " Strong isoprene emission response to temperature in tundra vegetation " published in the journal Proceedings of the National Academy of Sciences of the USA 119: e2118014119 https://doi.org/10.1073/pnas.2118014119 The tab-delimited file contains direct surface-atmosphere isoprene fluxes, measured every 30-minutesby Eddy Covariance with a Proton Transfer Reaction -Time of Flight- Mass Spectrometer (PTR-ToF-MS) during the whole growing season at two different tundra sites in Scandinavia (near Abisko, Sweden in 2018, and near Finse, Norway during 2019). It also contains the MEGANv2.1 biogenic model predicted isoprene emissions for the same periods and sites. In addition, air temperature, vegetation surface temperature, and photosynthetic photon flux density (PPFD) measured at the sites are also reported, together with their past 24h and 240h averages (needed to run the MEGAN simulation accounting for the recent past environmental conditions). This research has been supported by the European Research Council (TUVOLU – Tundra biogenic volatile emissions in the 21st century, grant no. 771012) under the European Union's Horizon 2020 research and innovation programme, the Independent Research Fund Denmark | Natural Sciences (DFF–4181-00141), and by the Danish National Research Foundation (CENPERM DNRF100). R.S. acknowledges a Ramón y Cajal grant (RYC2020-029216-I) funded by MCIN/AEI/10.13039/501100011033 and by "ESF Investing in your future". IDAEA-CSIC is a Severo Ochoa Centre of Research Excellence (MCIN/AEI, Project CEX2018-000794-S). This work is a contribution to the strategic research initiative LATICE (Faculty of Mathematics and Natural Sciences, University of Oslo, project number UiO/GEO103920) and was supported by the EMERALD project funded by the Research Council of Norway (project number 294948). High frequency wind data from Abisko was provided by ICOS-Sweden which has been co-financed by the Swedish Research Council (2019-00205); Abisko-Stordalen has been hosted by ANS and ...